Comparative Evaluation of Cytotoxicity of Fluoride Varnish as Root Canal Sealer against L929 Mouse Fibroblasts with Conventional Endodontic Sealers - Erfan Hosseini; Mahdi Lomee; jamshid Yazdani charati; Abolfazl Hosseinnataj; salma omidi (Mashhad University of Medical Sciences, 2021)
Introduction: This study aimed to assess the cytotoxicity of Duraflur fluoride varnish as root canal sealer against L929 mouse fibroblasts in comparison with four commonly used conventional endodontic sealers in the first 48 hours of exposure. Methods: In this in vitro, experimental study, L929 mouse fibroblasts were exposed to 1/1, ½, ¼ , and 1/8 concentrations of Duraflur fluoride varnish, AH Plus, Fill Canal, MTA Fillapex, and AH26 sealers. After 48 hours, the methyl thiazolyl tetrazolium (MTT) assay was performed to assess the cytotoxicity of sealers. Cell viability was determined as the percentage of viable cells compared with the control group. The results were analyzed using one-way ANOVA followed by the Tukey's post hoc test for multiple comparisons.. Results: MTA Fillapex had the lowest and AH26 had the highest cytotoxicity (p <0.05). Fluoride varnish showed high cell viability in 1/8 concentration (91.09%). Its cytotoxicity was close to that of AH Plus with no significant difference (P=0.49) but it had higher cytotoxicity than Fill Canal and Fill Apex (p <0.05). Fluoride varnish in 1/1 and 1/8 concentrations showed significantly higher cell viability than AH26 (p <0.001). Conclusion: Fluoride varnish sealer has acceptable biocompatibility comparable to that of conventional sealers. It has lower cytotoxicity than AH26.